СALPROTECTIN CONTENT UNDER THE DEVELOPMENT OF CROHN'S DISEASE AND NONSPECIFIC ULCERATIVE COLITIS - Горелая, Марина (SWorldJournal, 2021)
The research and diagnostic value of determining and monitoring the calprotectin protein content of in the human feces are considered in the work. Modern, sensitive and specific research methods were used: methods of solid-phase enzyme-linked immunosorbe